Prosecuting Executive Branch Wrongdoing - Cook, Julian A. (2021)
Attorney General William Barr's handling of Robert Mueller's Report on the Investigation into Russian Interference in the 2016 Presidential Election was undeniably controversial and raised meaningful questions regarding the impartiality of the Department of Justice. Yet, Barr's conduct, which occurred at the conclusion of the Mueller investigation, was merely the caboose at the end of a series of controversies that were coupled together from the outset of the investigation. Ensnarled in dissonance from its inception, the Mueller investigation was dogged by controversies that ultimately compromised its legitimacy. Public trust of criminal investigations of executive branch wrongdoing requires prosecutorial independence. To further this critical objective, an investigative and Prosecutorial structure must be implemented that grants a Prosecutor sufficient latitude to pursue independent investigations while reigning in the exercise of runaway discretion. Indeed, at no time since Watergate has there been such a clear need for reform. This Article will explain why many of the controversies that beset the Mueller investigation can be sourced to the Special Counsel regulations-the rules that governed his appointment, as well as his investigative and prosecutorial authority. And it will explain why many of these ills can be ameliorated by enacting a modified and innovative version of the expired Independent Counsel Statute